Saudi teachers 'knowledge and implementation of transitional skills and transition planning for students with autism spectrum disorder in Saudi Arabia. - Almughyiri, Salman (International Journal of Developmental Disabilities, 2026)
Objectives: The aim of the research is to study the teachers of those with autism spectrum disorder (ASD) reported knowledge of the transition skills and their implementation in transition planning. This research intends to increase the understanding of teachers' knowledge of transition skills and implementation in transition planning students with ASD when assisting them to become more independent and prosperous in life. Methods: The study applied a quantitative method using a survey as a research tool. The researcher used a survey as a research instrument given the study approach. The study population was male and female teachers who work with students with ASD in Riyadh. The number of participants that completed the survey was 187 teachers out of a population of 311 in Riyadh province of KSA, 101 females, and 86 males. This implies that 59% of the population participated in the study. All the participants were teachers of students with ASD in high school. Results: The research findings substantially contribute to the literature on the topic in multiple ways. Using targeted study questions, the findings of the research indicate that the respondents reported above-average knowledge of transition skills. The data showed that the subjects had adequate levels of conceptual and theoretical foundations of transition skills. Conclusions: This study emphasis on the needs to enhance teaching techniques and assisting students with ASD in making the transition to adulthood.